2018
DOI: 10.3233/thc-174717
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sitting posture on the loads at cervico-thoracic and lumbosacral joints

Abstract: BACKGROUND: The sitting in an awkward posture for a prolonged time may lead to spinal or musculoskeletal disease. It is important to investigate the joint loads at spine while sitting.OBJECTIVE: The purpose of this study was to investigate the joint moment and antero-posterior (AP) reaction force at cervico-thoracic and lumbosacral joint for various sitting postures.METHODS: Twenty healthy males participated in this study. Six sitting postures were defined from three spinal curvatures (slump, flat, and lordosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 36 publications
(35 reference statements)
1
34
0
7
Order By: Relevance
“…This causes a posterior movement of the nucleus pulposus that pushes onto the wall of the fibrous ring, with a risk of protrusion and possibly damaging the ring. Finally, (d) increased tension in posterior ligaments, especially due to muscle relaxation [20,21,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This causes a posterior movement of the nucleus pulposus that pushes onto the wall of the fibrous ring, with a risk of protrusion and possibly damaging the ring. Finally, (d) increased tension in posterior ligaments, especially due to muscle relaxation [20,21,26].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that Quintana-Aparicio et al [25] already demonstrated how students between 8 and 10 years of age sat in hyperkyphosis in more than half of the cases when listening to the teacher. It is important because if the slump is continued for a long time, it may cause pain and diseases at the cervicothoracic and lumbosacral joints [26]. Slump sitting position is associated with an increase in the spinal load [8,21], and there is greater pressure on the intervertebral disc than in the neutral posture [27,28] and a concentration of stress that can produce degeneration [22,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Manual therapy as a treatment for vertebral syndromes has been described by many authors. At the same time, MT in the form of monotherapy is inferior to complex treatment with the use of MT and physical rehabilitation [10,11,13].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, in recent years there have been quite a lot of works devoted to the gradual rehabilitation treatment for patients with neurological signs of degenerative-dystrophic pathology (DDP) of the spine [4,10,12,13]. However, most of them were dedicated to the treatment of patients with lumbar osteochondrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Всі ці питання підлягають вивченню та впровадженню в практику нових, більш ефективних комплексних заходів, в тому числі і з використанням МТ і кінезотерапії. Роботи, присвячені удосконаленню діагностичних і лікувальних заходів вертебральних больових синдромів, є актуальними [4,[10][11][12][13].…”
Section: вступunclassified